IMPLEMENTASI SAK SYARIAH DALAM LAPORAN KEUANGAN KOPERASI PENGKREDITAN RAKYAT SYARIAH (KPRS) - Ula, Nimatul; Nawirah, Nawirah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study is to determine the suitability of the presentation of the An-Nahl Pandaan KPRS financial statements to Syaria FAS. This research uses descriptive qualitative research in which the purpose is to describe and illustrate the application of Sharia Financial Accounting Standards in terms of the financial statements prepared by KPRS An-Nahl Pandaan. The techniques used in data collection are through observation, interviews, documentation, and online data search techniques. The results of the analysis and discussion of this study indicate that most of the financial statement presentations in KPRS An-Nahl are in accordance with Sharia FAS even though only the entity only reports the financial position (Balance Sheet). From the An-Nahl KPRS financial report that looks very prominent the discrepancy is that An-Nahl KPRS does not make the six other financial report components listed in the Sharia FAS because the KPRS An-Nahl management itself does not yet understand how to prepare financial reports in accordance with applicable standards.